ANSI/IEEE Std 430-1976 : IEEE Standard Procedures for the Measurement of Radio Noise from Overhead Power Lines (IEEE, 1976)
The purpose of this standard is to establish uniform procedures for the measurement of radiation of radio noise from overhead power lines with meters that conform to American National Standards. A uniform procedure is a prerequisite to comparisons of radio-noise performance of various overhead power lines. The procedure applies in the frequency range of 0.015 to 30 MHz. A procedure for measurements in the frequency range of 20 to 1000 MHz, which is to be used only as a guide, is also presented.